Cameroon - Agricultural Value Chain : Competitiveness Study - World Bank (Washington, DC, 2012)
This study, competitiveness of the value chain of the agricultural sector in Cameroon, aims to help the Government achieve its objectives for the rural sector. The main objective of this study was to provide information on the potentials, investment and growth policies of commercial agriculture in Cameroon. It gives an overview of the constraints and analyzes the national, regional or international competitiveness of six value chains of the agricultural sector. This paper examines family and large agro-industrial farms from different regions of Cameroon. The six aspects studied are: cassava, cotton, maize, palm oil, plantain and poultry. The primary purpose of this study of competitiveness is to identify products and operating systems already competitive or having the ability to become competitive on the domestic, regional or global market. The Government has explicitly asked the Bank to support new projects of its agricultural program. This economic and sectoral work will serve as a basis for a new loan to the agricultural sector of Cameroon.